Discriminatory Power of Women S Handball Game-Related Statistics at the Olympic Games (2004-2016) - Garcia-Hermoso, A (Polish Academy of Science, Committee of Physical Culture, 2018)
Sports performance analysis has been a growing field of study in the last decade. However, the number of studies in handball is small. The aims of this present study were (i) to compare handball game-related statistics by the match outcome (winning and losing teams) and (ii) to identify characteristics that discriminated performance in elite women s handball. The game-related statistics of the 236 matches played in the last four Olympic Games (Athens, Greece, 2004; Beijing, China, 2008; London, United Kingdom, 2012; and Rio de Janeiro, Brazil, 2016) were analysed. Differences between match outcomes (winning or losing teams) were determined using the chi-squared statistic, also calculating the effect sizes of the differences. A discriminant analysis was then performed applying the sample-splitting method according to match outcomes. The results showed the differences between winning and losing teams were red cards and assists. Also, the discriminant analysis selected five variables (shots, goalkeeper-blocked shots, technical fouls, steals, and goalkeeper-blocked fast-break shots) that classified correctly 83% of matches. The selected variables included offensive and defensive predictors. Coaches and players can use these results as a reference against which to assess their performance and plan training. © 2018 Editorial Committee of Journal of Human Kinetics, published by Sciendo 2018.